A novel multiplex assay amplifying 13 Y-STRs characterized by rapid and moderate mutation rate. (March 2015) - Rogalla, Urszula; Woźniak, Marcin; Swobodziński, Jacek; Derenko, Miroslava; Malyarchuk, Boris A.; Dambueva, Irina; Koziński, Marek; Kubica, Jacek; Grzybowski, Tomasz
Highlights: Thirteen carefully selected Y-STRs are capable of differentiating fathers and sons in ca. 16% of cases. The newly designed 13 Y-STR assay successfully amplifies 0.5–1 ng of DNA. Rapidly mutating Y-STRs aid lineage differentiation in populations characterized by low genetic diversity. Abstract: As microsatellites located on Y chromosome mutate with different rates, they may be exploited in evolutionary studies, genealogical testing of a variety of populations and even, as proven recently, aid individual identification. Currently available commercial Y-STR kits encompass mostly low to moderately mutating loci, making them a perfect choice for the first two applications. Some attempts have been made so far to utilize Y-STRs to provide a discriminatory tool for forensic purposes. Although all 13 rapidly mutating Y-STRs were already multiplexed, no single assay based on single-copy markers allowing at least a portion of close male relatives to be differentiated from one another is available. To fill in the blanks, we constructed and validated an assay comprised of single-copy Y-STR markers only with a mutation rate ranging from 8 × 10 −3 to 1 × 10 −2 . Performance of the resulting combination of nine RM Y-STRs and four moderately mutating ones was tested on 361 father–son pairs and 1326 males from 9 populations revealing an overall mutation rate of 1.607 × 10 −1 for the assay as a whole. Application of the proposed 13 Y-STR set to differentiation of haplotypes present among homogenous population of Buryats resulted in a threefold increase of discrimination as compared with 10 Y-STRs from the PowerPlex ® Y.